Pendidikan Islam Kontemporer Dalam Nasehat Luqman - Salsabila, Selvi; Alviona, Chelsyla; Harahap , Eli Nuraisyah; Yusriyah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
Character education in Islam has an important role in shaping the personality of students who have faith, morals and are socially responsible. However, in contemporary Islamic educational practice, the practice of character values is increasingly weakened. This research aims to examine the values of education in QS. Luqman:12-19 and sees its relevance to today's educational challenges. Using literature study methods and a descriptive qualitative approach, this research found that Luqman's advice contained important values such as monotheism, gratitude, respect for parents, amar ma'ruf nahi munkar, and humility. These values are conveyed through effective educational methods such as example, dialogue of affection, parables, and habituation. This research concludes that character education comes from QS. Luqman:12-19 is very relevant to be integrated into contemporary Islamic education as an effort to build a spiritually, socially and morally strong generation.